Circulating tumor cells in advanced non-small cell lung cancer patients are associated with worse tumor response to checkpoint inhibitors. Issue 1 (10th July 2019) - Tamminga, Menno; de Wit, Sanne; Hiltermann, T. Jeroen N.; Timens, Wim; Schuuring, Ed; Terstappen, Leon W. M. M.; Groen, Harry J. M.
Abstract : Background: Non-small cell lung cancer (NSCLC) patients treated with checkpoint inhibitors show long lasting responses, but it is hard to predict which patients will profit from this treatment with the currently used marker, programmed death ligand 1 (PD-L1). We hypothesized that circulating tumor cells (CTC) or tumor derived extracellular vesicles (tdEV) are markers of treatment efficacy. Methods: Patients with advanced NSCLC treated with checkpoint inhibitors were included. Blood was drawn at baseline (T0) and at 4 weeks of treatment (T1) for analysis of CTC and tdEV using CellSearch®. Tumor response was classified as partial or complete response based on the response evaluation criteria in solid tumors (RECISTv1.1) measured 4–6 weeks after start of treatment. Durable response was defined as stable disease, partial or complete response without disease progression at 6 months. Analyses were adjusted for covariables including PD-L1 expression. Results: We included 104 patients (30 with a tumor response, 74 non-responders, 2 responses not evaluable due to early death); 63 patients provided T1 samples. All patients were treated with PD-L1 inhibitors. The majority of patients received second (85%) or third line (treatment with nivolumab monotherapy (89%). CTC were present in 33/104 patients at T0 (32%) and 17/63 at T1 (27%), 9/63 patients had CTC (14%) at both time points. The presence of CTC, both at T0 (OR = 0.28, p  = 0.02, ) and T1 (OR = 0.07, p  < 0.01), was an independent predictive factor for a lack of durable response and was associated with worse progression free and overall survival. More tdEV were associated with shorter survival but not with response rate. Conclusion: CTC occur in one third of advanced NSCLC patients and their presence is a predictive factor for a worse durable response rate to checkpoint inhibitors. tdEV are associated with shorter survival but not with response.